CONDITIONS OF FORMATION OF SOCIAL PARTNERSHIP IN THE CONTEXT OF TRAINING OF COMPETITIVE SPECIALISTS (Education in the 21st Century, 2023)
The article discusses the functioning of social partnership and indicates that one of the conditions for the development of social partnership in Ukraine should be the formation and development of civil society and its institutions - public organizations, movements, trade union associations, political parties, etc.The author highlighted the factors that ensure the effectiveness of social partnership and suggested ways of formation, in particular: to ensure social partnership in Ukraine, the author considers the following to be necessary for: “Quality of training specialists in the profession”: improvement of legislation, including in the field of education; increasing targeted funding for monitoring studies; development of educational and professional standards of the new generation.For the tool “New specialties at the request of society”, the author has implemented through the creation of regional vocational training systems, the introduction of a system for collecting data on the labor market; identifying funding mechanisms for training; attracting marketers to regional training systems to determine the needs of the sector.In the direction of the “Contractual Form for Implementing Partnerships”, the article is determined by strengthening the educational legislation with regards to enhancing the implementation of the contractual form of implementing partnerships; creating conditions for increasing the number of subjects supporting scholarship funds policy; ensuring the functioning of the National Fund for Research, improving the financing of educational programs for the training of specialists on the basis of the qualification requirements established jointly with entrepreneurs.In order to ensure social partnership in the direction of “Improving the practical training procedure for students and trainees in enterprises and organizations”, it was proposed to create additional conditions.Providing social partnership in the field of "Informatization of the economy" most of all others focused on creating legal, organizational, financial and personnel conditions.
Keywords: social partnership, institution of professional education, employer, professions, la-bor market